The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40463-017-0196-0
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery with radial forearm free flap reconstruction: case control analysis

Abstract: BackgroundThe resection of large oropharyngeal tumors traditionally involves a lip-splitting mandibulotomy for adequate margin visualization and free flap reconstruction of the surgical defect. Transoral robotic surgery (TORS) has emerged as a technique that can resect large and complex oropharyngeal tumors, avoiding a lip-splitting approach. The aim of this study is to compare the lip-splitting mandibulotomy approach versus TORS for the management of advanced stage oropharyngeal carcinomas.MethodsProspectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 51 publications
0
54
1
4
Order By: Relevance
“…Some cases may require lateral pharyngotomy approach or lip-splitting anterior mandibulotomy for mandibular swing approach. Combined approaches such as transoral robotic surgery and lateral pharyngotomy with radial forearm free flap reconstruction may avoid the need for lip-splitting approach 54 . Treatment for advanced disease might produce the need for temporary tracheostomy and gas- Figure 5 Cranio-facial CT scan and contrast enhanced MRI scan of the patient.…”
Section: Oropharyngeal (Tonsillar) Cancermentioning
confidence: 99%
“…Some cases may require lateral pharyngotomy approach or lip-splitting anterior mandibulotomy for mandibular swing approach. Combined approaches such as transoral robotic surgery and lateral pharyngotomy with radial forearm free flap reconstruction may avoid the need for lip-splitting approach 54 . Treatment for advanced disease might produce the need for temporary tracheostomy and gas- Figure 5 Cranio-facial CT scan and contrast enhanced MRI scan of the patient.…”
Section: Oropharyngeal (Tonsillar) Cancermentioning
confidence: 99%
“…Kucur et al reported that among 113 OPC patients treated with TORS, six (5%) developed communications that were closed by submandibular gland or adjacent muscular pedicle flaps (28). For larger communications, a free flap may also be deployed robotically for closure (29).…”
Section: Clinical Applications Of Torsmentioning
confidence: 99%
“…The treatment of OPSCC with a primary TORS approach offers a number of advantages. TORS provides excellent access and visibility to for oropharyngeal resection while preserving neuromuscular structures important for swallowing (4,21). Despite the use of conformal techniques, xerostomia and dysphagia remain common morbidities with significant impacts on quality of life (11,27).…”
Section: Discussionmentioning
confidence: 99%